JOURNAL OF GOVERNMENT & POLITICS : The Political Power in Clash of Clans (COC) Vis-a-vis the Philippine Concept of Political Power - Jann Anthony A. Mag-Abo , Joy Melyn J. Porquis (FISIPOL UMY, 2016)
The Study wads focused primarily on the concept of political power which was viewed through the virtual and actual world using the strategy of simulation.